Dieta de Craugastor raniformis Boulenger (Anura: Craugastoridae) en un area con bosque seco tropical del norte de Colombia - Blanco-Torres, Argelina; Duré, Marta; Bonilla, María Argenis (Instituto de Ecología, A.C., 2015)
We characterize the diet of Craugastor raniformis, a terrestrial frog that inhabits the tropical dry forest in Colombia. The diet is constituted mostly of orthopterans, millipedes, arachnids and ants. Considering the morphological characteristics of this species, diet composition, gut vacuity index, trophic niche breadth and diversity, we consider this species would behave like a sit and wait predator.